HUBUNGAN ANTARA METAKOGNISI DAN MOTIVASI BERPRESTASI DENGAN KREATIVITAS - Matulessy, Andik (Persona:Jurnal Psikologi Indonesia, 2012)
Abstract, The research was conducted to find out the relationship between the metacognition and the achievement motivation and the creativity. The subject of the research was the first semester students of Counseling Department academic year 2011/2012 Nusantara PGRI University Kediri. The instrument used was the creativity scale, the metacognition scale, and the achievement motivation scale. The result of the research showed that metacognition and achievement motivation was significantly associated with the creativity shown by the calculated F value 63,084 and the significance of 0,000 (<0,05). The result of determination is 0,508. It means that 50,8 % independent variables (metacognition and achievement motivation) gave contribution to dependent variable (creativity). The result of partial correlation analysis showed that there is a very significant relationship between metacognition and creativity. There is a very significant positive relationship between achievement motivation and creativity.Â Keywords : creativity, metacognition, and achievement motivation